CALCULATION OF SOLID SECTION ELEMENTS UNDER CENTRAL COMPRESSION ACCORDING TODIFFERENT STANDARDS - Бібік, В. М.; Бібік, М. В.; Василенко, І. М. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Analysis of different calculating models of the elements of solid section under central compression according to SNIP II-23-81 * DBN B.2.6-163 and EN 01.01.1993 was presented. The comparison of calculations results for I-type, T-type and tube section elements was made. Differences between various standards are declared. Keywords:solid cross-section, central compression, stability of elements.